First record of Genus Sphenoderia Schlumberger, 1845 (Phylum Cercozoa: Euglyphida) from India - Purushothaman, Jasmine; Biswas, Srijani (Zootaxa, 2026)
The genus Sphenoderia Schlumberger, 1845 has been recorded for the first time in India. The type species Sphenoderia lenta Schlumberger, 1845 is noticed in the forest biotope of Arunachal Pradesh, and Sphenoderia minuta Deflandre, 1931 and Sphenoderia labiata Thomas & Gauthier- Lièvre, 1959 are recorded from the aquatic habitat of Meghalaya. All three species have been documented from the Northeastern region of India, highlighting the rich biodiversity found in this area. For each species, detailed descriptions and morphometry are provided based on the examination of specimens from the present study. Additionally, a global distribution review of the genus has also been discussed.